I know what I measure - Dwojak, Adam (Instal, 2023)
The most serious problem of companies operating pre-insulated networks is their maintenance in appropriate techni cal quality. Postponing repairs to an indefinite future often leads to occurrences in circuits measuring multiple moistu res, which makes the work of surveillance system diagnosticians very difficult, and in emergency situations leads to incorrect indications.